THE INFLUENCE OF PRODUCT REVIEWS, PRICES AND PAYMENT METHODS ON PURCHASE DECISIONS FOR SHOPEE APPLICATION USERS - Lilis Yuni Santia; Viniyati Maftuchach (SEAN Institute, 2022)
This study aims to determine the effect of product reviews, prices and payment methods on purchasing decisions of Shopee application users partially and simultaneously. This study was conducted to find out empirical evidence of the effect of product reviews, prices and payment methods on purchasing decisions for Shopee application users (study at STIE Muhammadiyah Jakarta). This type of research is causal by using primary data obtained from the results of the questionnaire. The population in this study were all shoppe customers in the STIE Muhammadiyah Jakarta, while the sample used was 100 respondents who were taken using probability sampling with the Lemeshow formula. The data analysis technique used in this study used a questionnaire method, for data processing using SPSS version 26 statistical software. The results of the t test show that partially product reviews, prices and payment methods have a significant effect on purchasing decisions. While simultaneously showing that product reviews, prices and payment methods affect purchasing decisions. Therefore, companies must pay attention to product reviews, prices and payment methods to influence purchasing decisions which will ultimately increase the company's revenue.